Gestão do uso da energia e do desempenho inovador sustentável na cadeia de suprimentos da indústria mineral - Camargo, Caroline Rossetto (2014)
The management of energy use has been used by industries of several market segments aiming to make their processes more sustainable and more competitive. There is a recurrent concern to combine business strategy with sustainable development in the present scenario. In this new configuration, innovation acts as a competitive differentiator, used to achieve quality, sustainability and efficiency in processes as well as products. Therefore, sustainable innovation becomes a strategic and economic factor for any industry that seek to achieve a high degree of sustainability, especially for the mineral industry due to their environmental and social impacts caused by mining activity and its importance for economic development of the country . From the proposed objectives and based on the theoretical assumptions of Liu et al. (2012), Gunday et al. (2011) and GRI (2006, 2010), we sought to identify management practices of energy use and sustainable innovation performance in the supply chain of the mineral industry. The research has a qualitative exploratory and descriptive approach, using a multicase study, which was developed from exploratory interviews and documentary research with five companies in the mineral sector. Among the main results, it was possible to highlight in two cases the adoption of management practices of energy use and its association with sustainable innovation performance. This attitude shows that Brazilian organizations of the mineral industry are seeking to meet environmental and social demands. In the remaining three cases, the main assumption of the study was not supported by the evidence.